Effectiveness of correction of eating disorders in anxiety-depressive disorders - Ogorenko, Вікторія; Kokashynskyi, Віктор (Psychosomatic Medicine and General Practice, 2023)
In most economically developed countries of the world, there is a clear tendency to increase the number of patients with anxiety-depressive disorders comorbid with eating disorders (ED), which lead to psychosocial maladjustment and a decrease in the quality of life. Depression is found in almost everyone and anxiety symptoms in every second patient among ED patients. Two-thirds of people suffering from anorexia had symptoms of anxiety-depressive disorders several years before the onset of ED. The purpose of the study was a comparative assessment of the effectiveness of treatment of eating disorders in patients with anxiety-depressive disorders, depending on the therapeutic and corrective measures. As a result of the study, it was established that there was no statistically significant difference between the main and the comparison group according to age and BMI. Statistically significant differences between the two groups were found for all other indicators. According to the results of the examination of the patients of the main group, a statistically significant difference was established between all indicators after 6 months. Among the patients of the comparison group, statistically significant positive dynamics were observed only in the indicators of the level of depression, personal and situational anxiety, and quality of life. According to the results of the correlation analysis of the main group, the indicator of the body image questionnaire had the largest number of direct correlations. After the intervention, some of the connections were lost and their strength generally decreased. Indicators of situational and personal anxiety, PHQ-9, indicators of restrained and emotional eating behavior had the largest number of direct connections. According to the obtained results, it is possible to ascertain the significant impact of the combined approach in the correction of ED in anxiety-depressive disorders. The obtained data indicate the effectiveness of the combined approach in view of the better results of therapy in all indicators in the main group. Correlation analysis showed a decrease in the strength of ties in the main group and their number after the intervention. In the treatment of anxiety-depressive disorders, the expediency of using a complex approach and the importance of paying special attention to the correction of symptoms of eating disorders have been proven.